PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESMENT, SATISFACTION) DENGAN METODE PENEMUAN TERBIMBING (GUIDED DISCOVERY) SUB POKOK BAHASAN LINGKARAN SMP KELAS VIII - Masruha, Siti; Sunardi, S; Kristiani, Arika Indah (Kadikma, 2013)
Abstract. The purposes of ARIAS (Assurance, Relevance, Interest, Assesment, Satisfaction) learning model are improving motivation, achievement and result of student learning. Guided discovery method has characteristics to improve the student’s abstract minds. The research aims to know process and result of development of mathematics learning materials based on ARIAS learning model with guided discovery method at sub topic of circle at grade eight of Junior High School. Learning materials development model refers to 4D Thiagarajan models. The products of this research are lesson plan, student book, worksheet, and evaluation test. Based on validation process and tryout the learning materials can be concluded that the learning materials had been appropriate with validate, practice, and effective criteria. Key Words : ARIAS learning model, Guided discovery method, Circle.